2015
DOI: 10.1098/rsif.2015.0319
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of collective changes in travel direction of starling flocks from individual birds' fluctuations

Abstract: One of the most impressive features of moving animal groups is their ability to perform sudden coherent changes in travel direction. While this collective decision can be a response to an external alarm cue, directional switching can also emerge from the intrinsic fluctuations in individual behaviour. However, the cause and the mechanism by which such collective changes of direction occur are not fully understood yet. Here, we present an experimental study of spontaneous collective turns in natural flocks of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 30 publications
(72 reference statements)
4
67
0
Order By: Relevance
“…Therefore, frontal individuals are more subjects to heading fluctuations and less inhibited to initiate U-turns. Similarly, in starling flocks, the birds that initiate changes in collective travelling direction are found at the edges of the flock [35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, frontal individuals are more subjects to heading fluctuations and less inhibited to initiate U-turns. Similarly, in starling flocks, the birds that initiate changes in collective travelling direction are found at the edges of the flock [35].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial suspensions [1], cellular monolayers [2] and sub-cellular filament/motor-protein mixtures [3,4] are continuously driven far from equilibrium through intrinsic energy injection by their biological constituent elements. This microscopic energy input can result in the spontaneous emergence of large-scale collective behaviour, including flocking [5][6][7], unidirectional flows [8], meso-scale turbulence [1,9,10], topological defect pair production [11][12][13], and phase separation [14]. Moreover there is a rapidly growing list of biological systems, including anterior-posterior establishment by active cytoplasmic streaming in oocytes [15], pupal wing morphogenesis [16], wound healing [17,18], and cancer invasion [19,20], that has been identified as leveraging collective flows for active self-organisation.…”
Section: Introductionmentioning
confidence: 99%
“…Information transfer is of particular relevance for collective behaviour, where it has been observed that small perturbations cascade through an entire group in a wave-like manner [62,63,34,3], with these cascades conjectured to embody information transfer [73]. This phenomenon is related to underlying causal interactions, and a common goal is to infer physical interaction rules directly from experimental data [36,30,35] and measure correlations within a collective.…”
Section: Introductionmentioning
confidence: 99%